Systematic Literature Review: Factors Influencing Generation Z's Attitudes Toward Environmentally Friendly Products and Their Implications for Green Consumer Behavior - Adah, Eva Fathussya; Nugroho, Arissetyanto; Rachbini, Widarto (International Journal of Science and Society, 2025)
This study examines the factors influencing Generation Z's attitudes toward environmentally friendly products and their implications for green consumer behavior, with a focus on reducing plastic waste in West Java, Indonesia. Through a Systematic Literature Review, this study analyzes recent scientific publications to identify patterns of relationships between environmental awareness, environmental knowledge, product availability, environmental policies, attitudes toward environmentally friendly products, and green consumer behavior. The review findings indicate that environmental awareness and knowledge play a fundamental role in shaping positive attitudes toward eco-friendly products. Product availability and effective environmental policies are crucial in bridging the gap between attitudes and behavior. While positive attitudes are a strong predictor of green consumer behavior, there remains a gap between attitudes and actual behavior. Digital technology and social media hold significant potential in influencing the attitudes and behavior of Generation Z. Cultural factors and geographical context also play a significant role. Implementation challenges such as price, convenience, and product availability remain major barriers. In conclusion, a holistic approach is needed that combines increased awareness, the provision of environmentally friendly products, effective policies, and the utilization of digital technology. Further research is required to explore effective strategies in specific contexts and address the attitude-behavior gap.